A NEW CARBONATITE OCCURRENCE IN NORTHERN TRANSBAIKALIA - Ripp G.S.; Badmatsyrenov M.V.; Skulyberdin A.A. (My University, 2002)
The hypothesis of the presence of carbonatites in northern Transbaikalia was substantiated. This gives rise to dramatic changes in the concept of the geologic history of this region. The occurrence is situated in the Muya block of Precambrian age. ne carbonatite body is up to 100 m. thick and about 450 m long and is confined to a zone of tectonic dislocations framing the wall of the Parama depression filled with Cenozoic deposits. The carbonatite is composed of ferroan dolomite, magnetite, and apatite and contains aegirine and orthoclase phenocrysts. Typical minor and accessory minerals are magnesioriebeckite, calcite, biotite, monazite, and pyrochlore. The carbonatites were formed in three stages. Magnetite content decreased and that of calcite increased from the earlier to later stages. The carbonatites are classed as beforsite on the basis of their mineralogical composition and ferrocarbonatite on the basis of their chemical composition. They associate with alkaline syenites and are accompanied by metasomatic rocks composed of potassic, feldspar, riebeckite, and biotite. The carbonatites contain up to 1.0-1.5% REE, 5.1% Sr, and 6-8% apatite. Most abundant among REE are the light lanthanides, which reside mainly in monazite and apatite containing up to 5 wt % REE. The main strontium-bearing phases are carbonates (dolomite and calcite) and apatite. The high concentrations of REE, apatite, and Sr in the carbonatites allow us to pose the problem of the economic reassessment of this and adjacent regions.